2020
DOI: 10.1128/mbio.00862-20
|View full text |Cite
|
Sign up to set email alerts
|

Conidial Melanin of the Human-Pathogenic Fungus Aspergillus fumigatus Disrupts Cell Autonomous Defenses in Amoebae

Abstract: The human-pathogenic fungus Aspergillus fumigatus is a ubiquitous saprophyte that causes fatal lung infections in immunocompromised individuals. Following inhalation, conidia are ingested by innate immune cells and can arrest phagolysosome maturation. How this virulence trait could have been selected for in natural environments is unknown. Here, we found that surface exposure of the green pigment 1,8-dihydroxynaphthalene-(DHN)-melanin can protect conidia from phagocytic uptake and intracellular killing by the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 47 publications
1
19
0
2
Order By: Relevance
“…In accordance with previous studies, phagosomelysosome fusion was found to increase in A. fumigatus pksP and rodA null mutants in both A549 and 16HBE airway epithelial cells, which is linked with a significant decrease in fungal survival [5,39,44,[63][64][65][66]. In A549 cells, no difference in spore uptake or phagosomelysosome fusion was observed in the rodB null mutant compared to wild type, even though both processes were enhanced in bronchial epithelial cells [55]. This high-resolution livecell imaging approach has also enabled us to observe digested A. fumigatus spores within airway epithelial cell phagolysosomes for the first time, as reported for spores contained within macrophages [14].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In accordance with previous studies, phagosomelysosome fusion was found to increase in A. fumigatus pksP and rodA null mutants in both A549 and 16HBE airway epithelial cells, which is linked with a significant decrease in fungal survival [5,39,44,[63][64][65][66]. In A549 cells, no difference in spore uptake or phagosomelysosome fusion was observed in the rodB null mutant compared to wild type, even though both processes were enhanced in bronchial epithelial cells [55]. This high-resolution livecell imaging approach has also enabled us to observe digested A. fumigatus spores within airway epithelial cell phagolysosomes for the first time, as reported for spores contained within macrophages [14].…”
Section: Discussionsupporting
confidence: 91%
“…In-vitro confrontation assays are typically visualized by microscopy, and manually observed and quantified, which is time consuming, where user variability and error occur across biological replicates. Additionally, these methodologies typically use macrophages as the model cell type to study fungal-host interaction and are performed using fixed samples which can alter the outcome of the interaction of Aspergillus with the host [51][52][53][54][55]. Here, we have combined a live-cell labelling strategy with automated 4D live-cell imaging to visualize and measure critical events required for Aspergillus clearance by the airway epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While in the ubiquitous humanpathogenic fungus Aspergillus fumigatus, the pathogen that causes fatal lung infection in immunocompromised individuals, produces both DOPA and DHN melanins (Langfelder et al 2003). The presence of DHN melanin in conidia protects from phagocytic uptake and ROS-induced intracellular killing by frugivorous amoeba Protostelium aurantium and disrupts its autonomous defense (Ferling et al 2020). In Sporothrix schenckii, production of DOPA melanin in the presence of tyrosine in fungal cell confers more resistance to nitrogen-derived oxidants and UV irradiation (Almeida-Paes et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism includes phagocytosis, reactive oxygen species (ROS) generations mediated by nicotinamide adenine dinucleotide phosphate-oxidase (NADPH), lactoferrin production, and neutrophil extracellular traps (NETs) formation ( Schoen et al 2019 ; Souza et al 2019 ; Shopova et al 2020 ). ROS production responds to swollen conidia, but not resting conidia, through NADPH oxidase activation ( Ferling et al 2020 ; Khani et al 2020 ). It has been demonstrated that the ROS-producing complex plays a crucial fungicidal role during A. fumigatus infection ( Shen et al 2016 ).…”
Section: Defense Mechanism Against a Fumigatusmentioning
confidence: 99%